2007
DOI: 10.1614/wt-06-064.1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Translocation Is the Cause of Antagonism of Glyphosate by MSMA in Browntop Millet (Brachiaria ramosa) and Palmer Amaranth (Amaranthus palmerii)

Abstract: Studies were conducted in growth chambers to characterize absorption and translocation of14C-glyphosate applied alone or in mixture with MSMA in browntop millet and Palmer amaranth. MSMA antagonized activity of glyphosate in both weed species. Absorption of14C-glyphosate in Palmer amaranth was rapid and increased with time from 11.1% at 0.5 h after treatment to 68.1% at 168 HAT. Absorption of14C-glyphosate in browntop millet ranged from 1.6% at 0.5 HAT to 39.1% at 168 HAT. MSMA in mixture with glyphosate did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…At this growth stage, meristematic regions for shoot and root growth in giant foxtail are very close physically. Similar translocation patterns of glyphosate have been observed in other grass species such as browntop millet [ Urochloa ramosa (L.) Nguyen] and barnyardgrass (Burke et al 2007; Kirkwood et al 2000).…”
Section: Resultssupporting
confidence: 68%
“…At this growth stage, meristematic regions for shoot and root growth in giant foxtail are very close physically. Similar translocation patterns of glyphosate have been observed in other grass species such as browntop millet [ Urochloa ramosa (L.) Nguyen] and barnyardgrass (Burke et al 2007; Kirkwood et al 2000).…”
Section: Resultssupporting
confidence: 68%
“…The C1B1 biotype absorbed similar levels of glyphosate (35 to 39% of applied), irrespective of herbicide treatment or harvest time. Burke et al (2007) recorded 57% (of applied) 14 Cglyphosate absorption in Palmer amaranth 48 HAT. Culpepper et al (2006) reported similar levels of absorption of glyphosate between resistant and susceptible biotypes.…”
Section: Control Bmentioning
confidence: 95%
“…Only 0.08 and 1.89% of the glyphosate translocated by brachiaria went to the roots of the weed, when associated to sugarcane and citrus, respectively, at 12 days after the application (Figures 2 and 3, respectively). In another Urochloa species, such as U. ramosa, only 10.8% of the applied radioactivity was translocated from the treated leaf to the rest of the plant (including the root) when glyphosate was applied in isolation 72 hours after treatment (Burke et al, 2007). These results show the small amount of the herbicide that reaches the root system of brachiaria.…”
Section: Resultsmentioning
confidence: 91%